Sterile Alpha Motif Domain-Mediated Self-Association Plays an Essential Role in Modulating the Activity of the Drosophila ETS Family Transcriptional Repressor Yan. - Zhang, J.; Graham, T.G.; Vivekanand, P.; Cote, L.; Cetera, M.; Rebay, I. (Molecular and Cellular Biology, 2010)
The ETS family transcriptional repressor Yan is an important downstream target and effector of the receptor tyrosine kinase (RTK) signaling pathway in Drosophila melanogaster. Structural and biochemical studies have shown that the N-terminal sterile alpha motif (SAM) of Yan is able to self associate to form a helical polymeric structure in vitro, although the extent and functional significance of self-association of full-length Yan remain unclear. In this study, we demonstrated that full-length Yan self associates via its SAM domain to form higher-order complexes in living cells. Introduction of SAM domain missense mutations that restrict Yan to a monomeric state reduces Yan's transcriptional repression activity and impairs its function during embryonic and retinal development. Coexpression of combinations of SAM domain mutations that permit the formation of Yan dimers, but not higher-order oligomers, increases activity relative to that of monomeric Yan, but not to the level obtained with wild-type Yan. Mechanistically, self-association directly promotes transcriptional repression of target genes independent of its role in limiting mitogen-activated protein kinase (MAPK)-mediated phosphorylation and nuclear export of Yan. Thus, we propose that the formation of higher-order Yan oligomers contributes to proper repression of target gene expression and RTK signaling output in developing tissues.